Introduction: A New Approach for Studying Political Contention – Contentious Episode Analysis - Hanspeter Kriesi; Swen Hutter; Abel Bojar; Argyrios Altiparmakis; Theresa Gessler; Sophia Hunger; Katia Pilati; Julia Schulte-Cloos (Contentious Episodes in the Age of Austerity: Studying the Dynamics of Government–Challenger Interactions, 2021)
On 24 May 2011, in the middle of the parliamentary debate on the so-called mid-term adjustment plan, yet another round of austerity imposed by Greece's international creditors, a call for a demonstration at Syntagma Square in Athens and at the White Tower in Thessaloniki appeared on Facebook. By the next day at least 20,000 people assembled in the two squares, mostly chanting “thieves, thieves” at parliamentarians and cursing the Parliament. The movement of the Greek Indignados or Aganaktismenoi was born. It would prove to be massive, expansive, and innovative. Immediately after the initial demonstrations, the main squares in the two cities were occupied, and simultaneous protests began in almost all major urban centers of the country. Interest would focus on Syntagma Square, however, where the occupation was symbolically confronting Parliament, juxtaposing the public assembly and the symbolic seat of political power. In the following days, the occupation grew exponentially, eventually reaching almost 400,000 participants on June 5th. In our dataset, there is an event associated with the Aganaktismenoi on almost every single day until the end of the episode on June 30th.
Keywords: 320